2020
DOI: 10.3390/app10072398
|View full text |Cite
|
Sign up to set email alerts
|

Lithographically-Fabricated HA-Incorporated PCL Nanopatterned Patch for Tissue Engineering

Abstract: Inspired by the aligned extracellular matrix and bioceramics in human bone tissue, we investigated the relative contributions of nanotopography and equine bone powders (EBPs) with human dental pulp stem cells (DPSCs) to the osteogenesis. Both nanotopography and EBPs independently promoted the osteogenesis of DPSCs, osteogenesis was further promoted by the two factors in combination, indicating the importance of synergistic design factor of guided bone regeneration (GBR) membrane. The osteogenesis of DPSCs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The addition of EBPs improved the hydrophilicity of the PCL membranes and facilitated cell diffusion and aggregation, while the nano grooves facilitated cell elongation. The growth and differentiation of human dental pulp stem cells (DPSCs) were enhanced by the synergistic effects of EBPs and nanopatterning; this is considered an effective method to boost the growth capacity of cells [43]. One drawback of PCL is its relatively low level of bioactivity that inhibits cell adhesion and growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of EBPs improved the hydrophilicity of the PCL membranes and facilitated cell diffusion and aggregation, while the nano grooves facilitated cell elongation. The growth and differentiation of human dental pulp stem cells (DPSCs) were enhanced by the synergistic effects of EBPs and nanopatterning; this is considered an effective method to boost the growth capacity of cells [43]. One drawback of PCL is its relatively low level of bioactivity that inhibits cell adhesion and growth.…”
Section: Resultsmentioning
confidence: 99%
“…Ye et al found that a higher electrospinning solution density increased the precipitation of Sr-CAP nanoparticles and increased the surface roughness of PCL/chitosan membranes [ 80 ]. In addition, to combat the drawbacks of the low bioactivity of PCL, Jang et al utilized the nano grooves to facilitate cell elongation [ 43 ]. The change of membrane mechanical strength depends on the distribution of nanoparticles, fiber diameter, and the interaction between nanoparticles and polymers [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, hydroxyapatite (HA), dicalcium phosphate (DCP) and α or β-tricalcium phosphate (α or β-TCP) have been utilized as bone substitutes. 5–11 In addition, natural sources, e.g. , sintered animal bones and clamshells, were also used in CPCs due to their similarity with native human bone.…”
Section: Introductionmentioning
confidence: 99%
“…4 To date, synthetic calcium phosphate (CaP) biomaterials and bioactive glasses, i.e., hydroxyapatite (HA), dicalcium phosphate (DCP) and a or b-tricalcium phosphate (a or b-TCP) have been utilized as bone substitutes. [5][6][7][8][9][10][11] In addition, natural sources, e.g., sintered animal bones and clamshells, were also used in CPCs due to their similarity with native human bone. They frequently used porcine, 12 bovine, 13 chicken, 14 and horse bone.…”
Section: Introductionmentioning
confidence: 99%